2012
DOI: 10.1051/0004-6361/201117955
|View full text |Cite
|
Sign up to set email alerts
|

First spectro-interferometric survey of Be stars

Abstract: Context. Classical Be stars are hot non-supergiant stars surrounded by a gaseous circumstellar disk that is responsible for the observed infrared-excess and emission lines. The phenomena involved in the disk formation still remain highly debated. Aims. To progress in the understanding of the physical process or processes responsible for the mass ejections and test the hypothesis that they depend on the stellar parameters, we initiated a survey on the circumstellar environment of the brightest Be stars. Methods… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
111
0
11

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(134 citation statements)
references
References 37 publications
12
111
0
11
Order By: Relevance
“…Howarth 2007). This idea is also supported by many interferometric observations, which have allowed to determine the oblateness of some Be stars (Domiciano de Souza et al 2003;Zhao et al 2011;Touhami et al 2011;Meilland et al 2012;Kraus et al 2012), suggesting that some of them are close to their critical rotation.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Howarth 2007). This idea is also supported by many interferometric observations, which have allowed to determine the oblateness of some Be stars (Domiciano de Souza et al 2003;Zhao et al 2011;Touhami et al 2011;Meilland et al 2012;Kraus et al 2012), suggesting that some of them are close to their critical rotation.…”
Section: Introductionmentioning
confidence: 59%
“…Rivinius et al (2006) showed that for the brightest shell stars of different spectral types, the mean fraction of the critical velocity is 81%, which corresponds to a mean ω higher than 0.92. Meilland et al (2012) found a mean value of ω = 0.95 for a sample of eight Be stars, considering V sin i and V crit from Frémat et al (2005) but i measurements derived from interferometry. Delaa et al (2011) deduced from interferometric observations of Be stars 48 Per and Ψ Per that both stars rotate at nearly critical rotation.…”
Section: Possible Link Between Very Rapid Rotationmentioning
confidence: 97%
“…This nonlinearity in the photometric response of the detector does not generate bias in the derived complex visibilities as explained by Delaa et al (2011). To model the spectrally resolved visibility and differential phase in the Hα emission line, we used the simple kinematic model developed for fast model-fitting of a geometrically and optically thin equatorial disk in rotation described in detail by Delaa et al (2011) and Meilland et al (2012).…”
Section: Spectrally Resolved Hα Data and Model Fittingmentioning
confidence: 99%
“…Studies of individual stars, based on nonradial pulsation modes (Cameron et al 2008;Saio 2013) and rotational rates inferred from interferometric data (Meilland et al 2012;Domiciano de Souza et al 2014), produce estimates of Ω/Ω c ranging from 0.60 to 0.98, which correspond to linear velocities ratios 0.44 V/V c 0.88 (V c is the critical equatorial linear velocity) or to ratios of centrifugal to gravity accelerations 0.14 a c /a g 0.70. These rates suggest that the surface rotational velocities of Be stars are undoubtedly very high, but they are not necessarily critical.…”
Section: Introductionmentioning
confidence: 99%